2006
DOI: 10.4141/s05-082
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and function of fungi in peatlands: A carbon cycling perspective

Abstract: Thormann, M. N. 2006. Diversity and function of fungi in peatlands: A carbon cycling perspective. Can. J. Soil Sci. 86: 281-293. Peatlands are a dominant landform in the northern hemisphere, accumulating carbon in the form of peat due to an imbalance between decomposition and plant production rates. Decomposer (saprobes) and mycorrhizal fungi significantly influence carbon dynamics by degrading organic matter via the synthesis of extracellular enzymes. As organic matter decomposes, litter quality variables fig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
110
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 136 publications
(154 reference statements)
18
110
1
2
Order By: Relevance
“…This finding is contrary to prior cultivation-dependent studies, which suggested that surface peatlands with extensive hyphal growth are usually dominated by fungal biomass (29,72). Our qPCR values simply represent ratios of fungal/bacterial SSU gene abundance, instead of biomass.…”
Section: Discussioncontrasting
confidence: 68%
“…This finding is contrary to prior cultivation-dependent studies, which suggested that surface peatlands with extensive hyphal growth are usually dominated by fungal biomass (29,72). Our qPCR values simply represent ratios of fungal/bacterial SSU gene abundance, instead of biomass.…”
Section: Discussioncontrasting
confidence: 68%
“…Quite unexpectedly, sequences similar to the common and fast growing genera Mucor and Penicillium were not detected at any of our sites (II, IV, V) even though their presence in peatlands has been confirmed elsewhere (e.g., Given and Dickinson 1975, Thormann 2006a, 2006b. It is unlikely that these genera would be entirely absent from Lakkasuo and Suonukkasuo, but they are certainly not abundant (II).…”
Section: Fungal Communitymentioning
confidence: 58%
“…Cellulose-degrading fungi are more abundant in peatlands than their bacterial counterparts (Hiroki and Watanabe 1996) and nowadays fungi are considered to be the main aerobic decomposers in these habitats (e.g., Thormann 2006aThormann , 2006b). In pristine wet peatlands, fungal decomposers are mostly limited to the uppermost surface layers (Latter et al 1967, Nilsson andRülcker 1992).…”
Section: Fungimentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect effects of WT drawdown on the composition and activity of aerobic microbial decomposers in peatlands via changes in plant community structure are, in spite of their significance, still poorly understood (Laiho, 2006;Thormann, 2006). Furthermore, soil nutrient availability may influence community-level decomposition processes (Hobbie and Gough, 2004).…”
Section: Introductionmentioning
confidence: 99%